1991
DOI: 10.1148/radiology.181.2.1924796
|View full text |Cite
|
Sign up to set email alerts
|

Palmaz stent in atherosclerotic stenoses involving the ostia of the renal arteries: preliminary report of a multicenter study.

Abstract: Palmaz balloon-expandable stents were placed in 28 hypertensive patients with atherosclerosis involving the ostia of the renal arteries. Stents were placed to treat elastic recoil immediately after conventional angioplasty in 20 patients and restenosis after percutaneous transluminal angioplasty in eight patients. Technical success (greater than 30% residual stenosis) was achieved in 27 patients. Complications occurred in five patients. At follow-up (1-25 months), hypertension was cured in three patients and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
92
1
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(99 citation statements)
references
References 0 publications
5
92
1
1
Order By: Relevance
“…In the mid-1980s, Palmaz et al [5] designed stainless steel stents to address atherosclerotic lesions in rabbits. Subsequent clinical studies showed the stents to be successful in subjects with obstructive lesions of coronary, iliac and renal arteries [6][7][8][9]. Mullins, O'Laughlin et al [10,11] introduced endovascular stents into pediatric practice.…”
Section: Introductionmentioning
confidence: 99%
“…In the mid-1980s, Palmaz et al [5] designed stainless steel stents to address atherosclerotic lesions in rabbits. Subsequent clinical studies showed the stents to be successful in subjects with obstructive lesions of coronary, iliac and renal arteries [6][7][8][9]. Mullins, O'Laughlin et al [10,11] introduced endovascular stents into pediatric practice.…”
Section: Introductionmentioning
confidence: 99%
“…The continue sutures predispose the vessel to pursiness in which the stagnation of the flow is possible. The end to side anastomosis is safer than end to end because with the end to end anastomosis the risk of stenosis three times is more common than the end to side anastomosis [3,4]. With making the expansion space between the first knotting and the vessel it will permit to the vessel to have place for expansion after removing the clamp (Figure 1-5) post removing the clamp there is no pursiness condition (Figure 4 and 6).…”
Section: Discussionmentioning
confidence: 99%
“…The vascular complications are two kinds: early and delayed, the early complication including stenosis and thrombosis. The early vascular complications are due to technical [2] which may be due to handling allograft vessel during procurement and irrigation (vessel trauma) and preparing recipient vessels (trauma) and anastomosing [3,4]. In kidney transplant anastomosing of the vessel may be carried out as end to end or end to side, end to side is less predisposes to stenosis [4].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] While restenosis occurs in > 50% of patients treated with percutaneous transluminal renal angioplasty, 9-11 restenosis rates of renal artery stents are only 10-25%. [2][3][4][5][6] As expected, the risk of renal artery stent restenosis is related to stent diameter, with larger stent diameters having lower rates of restenosis. Lederman et al demonstrated that renal stents with > 4.5 mm diameter had a 12% restenosis rate while renal stents of < 4.5 mm in diameter had restenosis rate of 21%.…”
Section: Case Reportmentioning
confidence: 99%
“…Renal artery stenting is the procedure of choice for treating atherosclerotic renal artery stenosis. [1][2][3][4][5][6][7][8] However, long-term benefits of renal artery stenting may be blunted by the development of stent restenosis, and the treatment of this condition is not well established, with limited therapeutic options. We present a case report of intravascular ultrasound-guided cutting balloon angioplasty (CBA) as a novel technique for the treatment of renal artery stent restenosis.…”
Section: Introductionmentioning
confidence: 99%